(untitled) (Journal of the College of Education for Women, 2019)
Revealing the relation betweensuicide and the degrees of hope loss at student of the university. In order to achieve the objective of this research , researcher erected measurement for suicide imagination and adopting Alinizi Measurement -2004 of hope loss for the university students .Researcher made adaptation for university students after assuring sincerity , steadiness and distinguishing abilities for the items of both mentioned measurements according to the sample ( 320 university students) were chosen randomly from six departments in the amount of three colleges in college of sciences for girls and three colleges in college of education for girls for two stages ( first & fourth ) . After treating the data statistically by using suitable statistical tools, research reached the following results ;There is positiverelationship between suicide imagination and hope loss .